Necesidad de reformar la ley orgánica de tránsito y transporte terrestre por atentar a los derechos y seguridad de las personas. - Luzuriaga Rojas, Magda Alicia (2013)
The Constitution of the Republic of Ecuador, recognized as fundamental rights of Ecuadorian citizens, among others: the right to legal security and the right to freedom of contract, which like all other rights established by constitutional must be respected and observed consistently for the duration of the order and social tranquility. However, the Land Transport Act, Traffic and Road Safety, and Insurance Regulation Mandatory Traffic Accident, contain some provisions concerning the insurance that contradict and threaten the fundamental rights referred to in paragraph prev. The obligation to hire the traffic accident insurance with insurers qualified only by the state imposed under Article 3 of Regulation General Insurance Mandatory Traffic Accident, promulgated Executive Order No. 809 issued by the economist Rafael Correa Delgado, as the Constitutional President of the Republic of Ecuador, limiting the right to freedom of contract and leaves the possibility for users of insurance coverage against better shape their expectations and demands against the eventuality of a traffic accident. On the other hand the problems that have been taken to enforce the compulsory insurance of traffic accidents in Ecuador, cause no doubt, breach of the right to legal security of citizens, who do not receive adequate compensation for damage will cause this type of mishaps. The legal issues to which reference has been made in the above lines is studied in this research work which concludes with a proposal for legal reform through which seeks to ensure that compulsory insurance against accidents, meeting the goals for which it was incorporated under Ecuadorian law, and that citizens who are affected by a traffic accident to the damages they suffered, giving effect to the insurance contract. 